Time Is of The Essence: An Ishigurian Wrinkle in Temporal Universality - Călinescu, Amalia (Selangor Humaniora Review, 2021)
There are many unknowns in the long equation of life, yet it does not matter whether or not something is real as long it feels natural to a person or a whole group, community, or nation. There is no unanimously approved key decoder of the mind, neither in reality nor in fiction, yet the psychotherapeutic potential of good fiction can help readers change their lives for the better. The present paper provides an overview of Kazuo Ishiguro’s novels to determine the distorted nature of time from a holistic perspective. Science has demonstrated that reality is, in truth, probabilistic: All systems are in superposition before being observed, which is to say, they all manifest themselves, at the same time, in all the states they can be in before an observer decides upon one of these states through his/her perception. Tapping into the vast realms of memory from a higher standpoint can strengthen and regulate the connection between time and physicality. As Ishiguro demonstrates in his novels, the human body can keep perfect time – time scarcity is only an illusion created by a timeless yearning for affection, compassion, and mutual appreciation. The primary purpose of the current paper is to show that, when embraced with an open heart, temporal distortion constitutes a recalibrating corollary of the human mind meant to preserve human sanity and orientate human choices, decisions, and actions in the right direction. Regarded as temporal literature, Kazuo Ishiguro’s novels can thus help readers restore their temporality to its healthy distortion.